Cyber warfare techniques, tactics and tools for security practitioners - Andrees, Jason; Winterfeld, Steve (Syngress is an imprint of Elsevier, 2014)
This book explores the battlefields, participants, and tools and techniques used during today's digital conflicts. The concepts discussed provide those involved in information security at all levels a better idea of how cyber conflicts are carried out now, how they will change in the future and how to detect and defend against espionage, hacktivism, insider threats and non-state actors like organized criminals and terrorists